2018
DOI: 10.1111/sdi.12688
|View full text |Cite
|
Sign up to set email alerts
|

When is more frequent hemodialysis beneficial?

Abstract: The use of frequent hemodialysis (HD) is growing, with the hope of improving outcomes in end-stage renal disease. We narratively review the three randomized trials, 15 comparative cohort studies, and several case series of frequent HD that empirically demonstrate the potential efficacy and adverse effects of these regimens. Taken together, the randomized studies suggest frequent HD may result in left ventricular mass regression. This effect is most pronounced when left ventricular mass is abnormal, but attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(173 reference statements)
0
3
0
Order By: Relevance
“…HD treatment was found to lead patients to experience limitations and frustration frequently, because it imposes many restrictions such as changing one’s daily routine and body appearance, fluid control and modifications related to diet (Ottaviani et al , 2014). In addition, these patients mostly experience painful treatment for a long duration, have to intake medications and live daily with an incurable disease and its complications (Suri and Kliger, 2018). These problems may consequently affect the individuals’ level of hopefulness, so these patients experience death anxiety due to living under stressful conditions (Ottaviani et al , 2014), which may induce non-adherence to their medical guidelines and exacerbate their medical problems (Sohn et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…HD treatment was found to lead patients to experience limitations and frustration frequently, because it imposes many restrictions such as changing one’s daily routine and body appearance, fluid control and modifications related to diet (Ottaviani et al , 2014). In addition, these patients mostly experience painful treatment for a long duration, have to intake medications and live daily with an incurable disease and its complications (Suri and Kliger, 2018). These problems may consequently affect the individuals’ level of hopefulness, so these patients experience death anxiety due to living under stressful conditions (Ottaviani et al , 2014), which may induce non-adherence to their medical guidelines and exacerbate their medical problems (Sohn et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Though the studies have shown conflicting results regarding whether more frequent dialysis improves mortality, there are other benefits including regression of left ventricular mass (if it was abnormal earlier), improved blood pressure control, reduced use of antihypertensives, and better pregnancy outcomes. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest and subsequent research have grown on the topic of optimal hemodialysis frequency. Suri and Kliger consider when and in which patient frequent hemodialysis may be beneficial, while Mathew et al review the benefits and risks of a twice weekly or incremental approach to initiation of hemodialysis . While this Seminars in Dialysis issue focuses on the dialysis patient, it is recognized that renal transplantation provides better survival in most patient populations.…”
mentioning
confidence: 99%